Konsep Produksi Menurut Tan Malaka Ditinjau dari Perspektif Ekonomi Islam - MA, Zuwardi; Padli, Hardiansyah (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This research aims to depict Tan Malaka’s socialist economic thought related to the issues on the production of concept. This is qualitative research using library research method to gather the data on Tan Malaka’s thought on the concept of production. This study shows that the concept of the balance of production and consumption, the country's economic independence and the concept of labor costs in line with the concept of Islamic economics. While from the arrangement of land as a factor of production, Tan Malaka gradually wants to eliminate individual ownership of the means of production. This is not in line with Islamic economic concept where individual ownership of the means of production and production factors permitted as long as not contrary to Islamic law.